Impact of Apple Pulp on Textural Characteristics, Microstructure, Volatile Profile, and Sensory Acceptance of Yogurts - Dimitra Dimitrellou; Thomas Moschakis; Panagiotis Kandylis (Foods, 2025)
Fresh apple pulp from the Granny Smith variety was used at different levels (5–15% w/w) for yogurt production. Color, texture, microstructure, aroma, and sensory analyses were used to evaluate the effect of the apple pulp on the main characteristics of yogurt. Yogurts with apple pulp presented a lower brightness (L*) and an increased redness (a*) and yellowness (b*), which were significantly affected by the apple pulp concentration. The texture analysis revealed an improved consistency and reduced syneresis, leading to a creamier and more stable product. The aroma profile of yogurts was enriched, presenting higher ester contents. Confocal laser scanning microscopy showed that the incorporation of modest quantities of apple pulp resulted in the formation of initially denser networks, while at elevated levels, an enhanced microscopic phase separation occurred. A 5% apple pulp addition achieved a balance between enhancing flavor and texture retention while maintaining high overall acceptability, as was also confirmed by the sensory evaluation.